"The Japanese" in Colorado's racial discourse: fear, anxiety, and spectacle in the reporting of the Denver Post during the interwar years (1919-1941) - Tenn, Christopher, author; Henry, Todd, advisor; Jones, Elizabeth, committee member; Archie, Andre, committee member (Colorado State University. Libraries, 2010)
This thesis is comprised of two principle sections. The first two chapters examine the experiences of Japanese immigrants residing in Colorado during the sixty years prior to the onset of World War II. These chapters describe the characteristics of Colorado's Japanese communities, the circumstances which drew them to Colorado, and the demographic changes the community underwent in the decades preceding the Second World War. The way in which the racial background of these individuals shaped their experiences in Colorado is of central importance to this work. Chapters 1 and 2 analyze the ways in which race intersected with transnational politics, local economic contingencies, and cultural attitudes to influence the responses of Colorado's Euro-Americans to their Japanese neighbors, profoundly shaping the experiences of Japanese immigrants in Colorado. The latter half of this work analyzes racial discourses circulating in the Denver Post during the interwar years. During the two decades leading up to the Second World War, the Denver Post was the predominant regional newspaper and regularly featured articles on Japanese Americans, Japanese nationals, Japan, and Japanese culture and society. I argue that the sentiments expressed within the paper were representative of a popular racial discourse that was ultimately essentializing and dehumanizing. The language employed within this discourse lumped together a complex and diverse group of people into the racial category of "Japanese," attributing to that category a series of essential and universal characteristics. In my critique of this language, I reveal that this discourse was often multi-faceted and expressed sentiments that varied from fear and anxiety, to awe and fascination. The result was the production of numerous and varied stereotypes which served as representations of the "Japanese" to readers of Colorado newspapers. Regardless of what characteristics it projected upon the "Japanese," however, this discourse continued to homogenize all individuals of Japanese ethnicity into a singular racial entity, problematically reinforcing the legitimacy of race as a valid means of social categorization in the process. I am critical of such a category and, in this work, seek to demonstrate how the process of constructing a "Japanese" racial identity during the interwar years was in fact a process of othering that contributed to the ease with which negative, vilifying stereotypes were later projected upon Japanese Americans during the Second World War.
The Japanese in Colorado's racial discourse: fear, anxiety, and spectacle in the reporting of the Denver Post during the interwar years (1919-1941)
Covers not scanned.
Keywords: Japanese Americans -- Colorado -- History; Japanese Americans in mass media